DIGITALISATION CATALYST: THE ROLE OF ORGANIZATIONAL CULTURE IN PUBLIC SERVICE TRANSFORMATION - Jorry Karim; Rauf A. Hatu, Sastro Mustapa Wantu, Zuchri Abdussamad (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Digital transformation in the public service sector is a strategic step in increasing efficiency, transparency, and accountability of the bureaucracy. Organizational culture plays an important role in supporting the implementation of technology through strengthening values such as integrity, professionalism, and commitment. This study aims to analyze the role of organizational culture in driving the success of digital-based public service transformation, especially through the implementation of the Electronic-Based Government System in Gorontalo Province. With a qualitative approach and case study method, data were collected through observation, interviews, and document analysis. The results of the study indicate that the integrity of regional apparatus needs to be improved through stricter supervision and structured training. Professionalism still faces challenges in the form of a lack of technical competence and capacity development. The commitment of regional apparatus to digital transformation also needs to be strengthened through a collaborative and innovative work culture. This study concludes that the synergy between integrity, professionalism, and commitment is key to creating an organizational culture that supports sustainable digital transformation. Strategic recommendations include increasing digital-based training, strengthening monitoring mechanisms, and integrating organizational cultural values into policies to achieve more effective and responsive public services.